Fermentasi Anaerobik Biogas Dua Tahap Dengan Aklimatisasi dan Pengkondisian pH Fermentasi - Purwinda Iriani; Yanti Suprianti; Fitria Yulistiani (Politeknik Negeri Malang, 2017)
Generally, biogas production on the household scale is using one-stage anaerobic fermentation technology, which accommodates two main processes of biogas production, namely acetogenesis and methanogenesis. An obstacle of using one-stage biogas digester is the imbalance of the fermentation process that indicated by the increase of organic load rate and shorter retention time that lead to un-optimal biogas productivity. This research undertook the application of two-stage anaerobic digestion, supported by adjusting the initial pH for both acetogenic and methanogenic processes. Firstly, the research initiated by acclimatization (activation) process of acetogenic and methanogenic bacteria via fermentation in laboratory scale (19 L) digesters, separately. The results of acetogenic bacteria acclimatization process on cow dung media showed the pH stability needed for the reaction acetogenic, in the range of 5-6, while the control showed the pH changes still in the neutral pH range (6-7). The substrate from lab-scale acetogenic and methanogenic digester, then used as a starter for pilot-scale digester (125 L and 500 L, respectively). The mixture of water and cow dung were adjusted at initial pH 5.5 on acetogenic digester for 2 weeks. Those material were used for biogas production in the methanogenic digester. The result of the methanogenic process showed an increasing volume of biogas and the composition of methane (CH4) in the biogas. The highest CH4 composition was obtained on the 20th day, which reached 74.82%, and the highest volume of biogas production was at day 22, with the rate of 8.87 L/day. The highest energy potential obtained was 217.66 kJ/day.